2019
DOI: 10.5194/bg-16-255-2019
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting eddy covariance data from heterogeneous Siberian tundra: land-cover-specific methane fluxes and spatial representativeness

Abstract: Abstract. The non-uniform spatial integration, an inherent feature of the eddy covariance (EC) method, creates a challenge for flux data interpretation in a heterogeneous environment, where the contribution of different land cover types varies with flow conditions, potentially resulting in biased estimates in comparison to the areally averaged fluxes and land cover attributes. We modelled flux footprints and characterized the spatial scale of our EC measurements in Tiksi, a tundra site in northern Siberia. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 70 publications
2
62
0
Order By: Relevance
“…Furthermore, there is evidence that traditionally unmeasured surfaces (i.e., tree stems) are important sources of CH 4 to the atmosphere and could explain spatial heterogeneity within ecosystems (Barba et al 2019). Accurately representing spatial heterogeneity and the relative fraction of uplands and wetlands is imperative for interpreting and predicting CH 4 emissions within many ecosystems, and for upscaling flux measurements regionally and globally as wetlands are hot spots for carbon cycling (Treat et al 2018a;Tuovinen et al 2019;Rößger et al 2019). Flux footprint analysis characterizing the fractional coverage of the dominant surface types, particularly the fraction of open water and aerenchymatous plants, is important for interpreting EC CH 4 flux measurements and quantifying annual CH 4 budgets at spatially heterogeneous sites (Franz et al 2016;Helbig et al 2017a;Jammet et al 2017) (Fig.…”
Section: Ec Flux Data Quality Assessmentmentioning
confidence: 99%
“…Furthermore, there is evidence that traditionally unmeasured surfaces (i.e., tree stems) are important sources of CH 4 to the atmosphere and could explain spatial heterogeneity within ecosystems (Barba et al 2019). Accurately representing spatial heterogeneity and the relative fraction of uplands and wetlands is imperative for interpreting and predicting CH 4 emissions within many ecosystems, and for upscaling flux measurements regionally and globally as wetlands are hot spots for carbon cycling (Treat et al 2018a;Tuovinen et al 2019;Rößger et al 2019). Flux footprint analysis characterizing the fractional coverage of the dominant surface types, particularly the fraction of open water and aerenchymatous plants, is important for interpreting EC CH 4 flux measurements and quantifying annual CH 4 budgets at spatially heterogeneous sites (Franz et al 2016;Helbig et al 2017a;Jammet et al 2017) (Fig.…”
Section: Ec Flux Data Quality Assessmentmentioning
confidence: 99%
“…Data availability. The micrometeorological data used in this study can be accessed via the Zenodo data repository (Tuovinen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The eddy-covariance (EC) technique, a well-established method for the direct quantification of turbulent surfaceatmosphere exchange processes (Aubinet et al, 2012), can provide valuable information on current CH 4 flux rates between various types of ecosystems and the atmosphere (e.g., Taylor et al, 2018;Rößger et al, 2019;Tuovinen et al, 2019), including insights into processes and controls (e.g., Pirk et al, 2016;Kittler et al, 2017b;Neumann et al, 2019) that can be used to improve future projections. However, the data quality of EC measurements depends strongly on the adherence to several theoretical assumptions, e.g., steady-state conditions and horizontal homogeneity , which frequently limits data availability.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial heterogeneity in the emission patterns of methane surrounding the flux tower (e.g., Rey-Sanchez et al, 2019) may also lead to pronounced variability in the observed CH 4 flux time series (Tuovinen et al, 2019). Particularly for wetland ecosystems, ecosystem characteristics such as inundation level or vegetation composition may vary at the finest spatial scales (Muster et al, 2012;McEwing et al, 2015), creating microsite variability with strong gradients in methane emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation